Effect of long-acting testosterone undecanoate treatment on quality of life in men with testosterone deficiency syndrome: a double blind randomized controlled trial - Tong, S.F.; Ng, C.J.; Lee, B.C.; Lee, V.K.M.; Khoo, E.M.; Lee, E.G.; Tan, H.M. (2012)
This study aimed to investigate the effect of intramuscular injection of testosterone undecanoate on overall quality of life (QoL) in men with testosterone deficiency syndrome (TDS). A randomized controlled trial over a 12-month period was carried out in 2009. One hundred and twenty men aged 40 years and above with a diagnosis of TDS (serum total testosterone, <12 nmol l(-1) and total Aging Male Symptom(AMS) scores >= 27) were invited to participate. Interventions comprised intramuscular injection of either placebo or 1000 mg testosterone undecanoate, given at weeks 0, 6, 18, 30 and 42. This paper presents the secondary analysis of QoL changes measured in the scores of Short-Form-12 (SF-12) scale at baseline, weeks 30 and 48 after the first injection. A total of 56/60 and 58/60 men from the active treatment and placebo group, respectively, completed the study. At week 48, before adjusting for baseline differences, the QoL of men in the treatment group improved significantly in five out of the eight domains on SF-12. The physical health composite scores improved 4.0 points from a baseline of 41.9 +/- 7.0 in the treatment group compared to 0.8 point from a baseline of 43.7 +/- 7.1 in the placebo group (F=3.652, P=0.027). The mental health composite scores improved 4.4 points from a baseline of 37.1 +/- 9.0 in the treatment group compared to 1.0 points from a baseline of 37.6 +/- 7.9 in the placebo group (F=4.514, P=0.018). After adjusting for baseline differences, significant improvement was observed in mental health composite scores, but not in physical health composite scores. Long-acting testosterone undecanoate significantly improved the mental health component of QoL in men with TDS. Asian Journal of Andrology (2012) 14, 604-611; doi:10.1038/aja.2011.178; published online 28 May 2012